2004
DOI: 10.1074/jbc.m402031200
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine Transforming Growth Factor α Regulates Cell Adhesion by Multiple Signaling via Specific Phosphorylation Sites of p70S6 Kinase in Colon Cancer Cells

Abstract: Recently, we showed that autocrine transforming growth factor ␣ (TGF␣) controls the epidermal growth factor receptor (EGFR)-mediated basal expression of integrin ␣ 2 , cell adhesion and motility in highly progressed HCT116 colon cancer cells. We also reported that the expression of basal integrin ␣ 2 and its biological effects are critically controlled by the constitutive activation of the ERK/MAPK pathway (Sawhney, R. S., Sharma, B., Humphrey, L. E., and Brattain, M. G. (2003)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 33 publications
3
31
0
Order By: Relevance
“…Several recent studies have identified a critical role for the nPKC isoforms in the activation of S6K1 (41,47). In a recent study the novel PKC isoforms, PKC ε and PKC δ , but not the classical PKC isoforms, PKC α or PKC β , were shown to be involved in PE-stimulated S6K1 phosphorylation of adult rat cardiomyocytes (as measured through electrophoretic mobility shifting of S6K1) (41).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have identified a critical role for the nPKC isoforms in the activation of S6K1 (41,47). In a recent study the novel PKC isoforms, PKC ε and PKC δ , but not the classical PKC isoforms, PKC α or PKC β , were shown to be involved in PE-stimulated S6K1 phosphorylation of adult rat cardiomyocytes (as measured through electrophoretic mobility shifting of S6K1) (41).…”
Section: Discussionmentioning
confidence: 99%
“…GEO cells were cultured in a humidified incubator at 37°C for 3-4 days with 5% CO 2 in a chemically defined serum-free medium. At about 80% confluence, the medium was changed to supplemented McCoy's (SM) medium (8). Cells were harvested with trypsin (0.125%) at 37°C and pelleted by gentle centrifugation at 800 ϫ g in a clinical centrifuge.…”
Section: Methodsmentioning
confidence: 99%
“…GEO cells were grown in serum-free medium containing 4 g/ml transferrin and 20 g/ml insulin at 37°C with 5% CO 2 . For transient transfection experiments, cells were grown to 50 -60% confluence, medium was changed to SM, and transfections were carried out using FUGENE 6 according to our previous report (8). The ratio of FUGENE 6 to DNA was maintained at 10 l of FUGENE 6 to 2.5 g of DNA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, further experiments need to be performed to identify the components responsible for control of 5 0 TOP mRNA translation downstream of the PI3K pathway. Importantly, the activity of S6K1 and 2 is upregulated in tumors from different histological origins Sahin et al, 2004;Savinska et al, 2004;Sawhney et al, 2004;Surace et al, 2004) and, remarkably, cancer cells harboring mutations that aberrantly upregulate the PI3K/Akt pathway display a hyperactivation of S6K activity (Ruggero and Pandolfi, 2003;Stephens et al, 2005).…”
Section: Ribosomal Proteinsmentioning
confidence: 99%